Myth Creation and Audience Building from Davy Crockett to Chuck Norris: the Thin Line between Fact and Fiction - Tillman , Gábor (FOCUS: Papers in English Literary and Cultural Studies, 2010)
In 1835, Halley’s Comet re-approached the Earth after its seventy-year orbit. The whole world was anxious to find out what was going to happen, and if they were in any danger. According to a story from an 1837 almanac, Andrew Jackson, the President of the United States, found the best person to solve the comet question: Davy Crockett. Crockett was hired to “wring the tail off the comet before it could scorch the planet” (Hutton xxv). Apparently, he managed to do the job quite well. This is how he recounts the event: I did so, but got my hands most shockingly burnt, and the hair singed off my head, so that I was as bald as a trencher. I dived right into the Waybosh river, and thus saved my best stone blue coat and grass green small clothes. With the help of Bear’s grease, I have brought out a new crop, but the hair grows in bights and tuffs, like hussuck grass in a meadow, and it keeps in such a snarl, that all the teeth will instantly snap out of an ivory comb when brought within ten feet of it. (qtd. in Hutton xxvi)